Design of micro-wind turbine for stand alone application / Amirul Syafiq bin Zamry. - Amirul Shafiq Zamry (School of Electrical System Engineering, Universiti Malaysia Perlis, 2017)
In this project, the following objectives are set to be achieved ; to construct a hardware for micro-wind turbine with combination several wind turbine generators wind turbine with lower cost, modular and can be placed on small area ; to design circuit configuration of generator in series, parallel or series parallel to give best voltage and current output based on wind speed ; to implement a micro-wind turbine which can be operating at lower wind speed ; the first objective is to construct a hardware for micro-wind turbine with combination several wind turbine generators with lower cost, modular and can be placed on small area. The design of micro-wind turbine is in micro scale, therefore it can be located at any place that conventional wind turbine cannot be placed such as building, a rooftop house or so on. It is also design at lower cost since the cost of ordinary wind turbine are expensive ; the next objective is to design circuit of generator in series, parallel or series parallel in order to obtain optimum voltage and current output based on wind speed. This concept of micro-wind turbine inspired from Photovoltaic Solar cell which can arrange in series, parallel or array. These configurations would give an optimum voltage and current output. The last objective is to implementa micro-wind turbine prototype which can be operatingand generating electrical energy at low wind speed.